A comparative evaluation of structured and unstructured forms of viva voce for internal assessment of undergraduate students in Pharmacology - Khakhkhar, Tejas M.; Khuteta, Neelesh; Khilnani, Gurudas (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The study was designed to identify value of structured viva (SV) as an assessment tool, to ascertain its correlation with unstructured viva (UV) and to find relationship between viva and theory examination results. Methods: This prospective and observational study was conducted on a total of 135 students of the 2nd professional MBBS. All students faced two viva sessions (SV and UV), each of 10 marks on same topics in general pharmacology and autonomic nervous system. Time limit per student was 10 minutes. SV was conducted on pre-validated, standardized cards (n=40) with 5 questions in each card and 0.5 marks of each question. By draw of lots to be performed by students themselves, each student was given 4 cards. One week prior to the viva, the theory examination of 40 marks on same topics was conducted. Results: The mean marks of all students in SV (3.46±1.44) were significantly lower (P <0.0001) than those of UV (4.61±2.02). There was significant less deviation of mean marks in all groups of SV (P <0.05). The mean percentage marks of SV (34.63±14.37%) had similarities with results of theory examination (34.67±10.49%) (P=0.9720), while the difference between mean percentage marks of UV (46.15±20.19%) and theory was statistically highly significant (P <0.0001). Conclusions: SV increases objectivity and reduces subjectivity as compared to UV because of similar pattern of questions, difficulty levels and standardised scoring system. SV provides an opportunity to measure how well students can apply knowledge. Thus, SV can be used for formative and summative assessment.